THE ROLE OF THE GOVERNMENT IN MANAGING TOURISM OBJECTS IN WANGGAR BEACH, NABIRE CITY, CENTRAL PAPUA PROVINCE - Lasamahu, Hellena Griffith; Widodo, Aris; Palimbu, Lamba Toding (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to examine the role of the government in managing beach tourism attractions in Nabire Regency. Specifically, it seeks to identify how the government contributes to the management of these tourist sites, the factors that hinder effective management, and the solutions implemented to overcome these challenges. The research employs a quantitative design with a descriptive approach to provide a clear picture of the current situation. A saturated sampling technique was used, where the entire population was included as the sample, totaling 47 respondents. The focus of this study is the Beach Wanggar tourist attraction, which represents significant tourism potential for Nabire Regency but remains underdeveloped. Despite its natural appeal, the site has not received focused attention from local authorities, resulting in limited facilities and management efforts. By exploring both the obstacles and government strategies, this study aims to provide insights into improving the management of Beach Wanggar. Ultimately, the findings are expected to support better planning, enhanced facilities, and more sustainable tourism development in the region.